Paciente-limite: entre Winnicott e Green - Nichile, Felipe Ferreira de (2013)
The basis of this psychoanalytic research is the comparative analysis between the works of D. W. Winnicott and André Green regarding the Theoretical-Clinical proposals presented by the authors to the treatment of the borderline patient, whose behavior is often characterized by a refractory dynamic to the classical treatment proposed by Sigmund Freud. Therefore, we aimed to draw a parallel between the psychoanalytic treatment sessions conducted by each of the authors, having as reference the instigating case of a borderline patient they had in common. Based on the clinical interventions that both authors report about the case, we attempt to establish which were the main theoretical aspects that supported them, as to investigate which innovations the authors bring to this type of patient, to whom they created clinical dispositives compatible with what they understand to be this psychopathology. To that end we intent to establish their main points of convergence and divergence. We concluded then that despite being quite close in some aspects, the authors propositions are, to a large extent, quite heterogeneous theories and present quite divergent clinical proposals. According to Winnicott, the regression to the dependency is the emphasis of the treatment, as a way to resume the normal process of personal maturation, amended by a traumatic situation and that needs to be lived again in analysis, this time with the support of a favorable environment to this return. To Green, the treatment is based on the creation of analytical environment favorable to the processes of verbalization and symbolization, as a possibility to give meaning to the vicissitudes of the drives as a way to the internalization of negative